Server Dengan NodeMCU ESP8266 Berbasis Internet Of Things (IoT) Pada PT PLN Batam - Ferianto; Bobi Agustian (CV. Multi Kreasi Media, 2024)
The development of technology and science is currently growing rapidly. This is done with the aim of simplifying daily human work. Creating tools to be able to help and facilitate humans in carrying out their duties or lighten the human burden. This technology will involve microcontrollers and sensors. So the purpose of doing this research is to create a server room temperature control system based on the Internet of Things (IoT). The temperature controller automatically uses the DS18B20 sensor as a temperature gauge and a fan, as well as a buzzer as a sound notification if the temperature is more than the set temperature. The method used in the server room temperature monitoring system is using ADDIE. By specifying membership and rules in ESP8266 as the brain, it can set the temperature value. In the blynk system, it can produce output in the form of a graph of the server room temperature. The expected result is that if the temperature exceeds the set limit, the fan will spin and there will be a notification.